KEANEKARAGAMAN ETNIS DEWAN TATA KELOLA PERUSAHAAN REAL ESTATE INDONESIA - Ilona, Desi (Gapenas Publisher, 2024)
This study investigates the differences in board governance ethnic diversity between large and small real estate companies in Indonesia, a country known for its rich ethnic heterogeneity but lacking in inclusive representation within corporate leadership. Using a quantitative approach, the research examines ethnic diversity at both the supervisory board (SBED) and management board (MBED) levels. An observation of 364 real estate companies listed on the Indonesia Stock Exchange from 2004-2017, comprising 317 large and 47 small firms—was analyzed based on publicly available board composition data. Independent samples t-tests reveal a statistically significant difference in SBED between large and small companies, with smaller firms exhibiting higher ethnic diversity (p < 0.001, Cohen’s d = 0.464). However, no significant difference was found in MBED across firm sizes. The findings suggest that organizational size plays a critical role in shaping ethnic representation at the supervisory board level, likely due to differing governance structures and recruitment practices. These results have practical implications for corporate policy, particularly in encouraging inclusive governance practices in larger firms. The study highlights the need for greater transparency in diversity reporting and provides a foundation for future research on ethnic inclusivity in Indonesia’s corporate sector.